2002
DOI: 10.3402/tellusa.v54i5.12167
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and observations of the katabatic flow dynamics over Greenland

Abstract: The katabatic wind system over the Greenland ice sheet is studied using simulations of the hydrostatic Norwegian Limited Area Model (NORLAM) and measurements of an instrumented aircraft. The structure and the dynamics of the katabatic wind over the ice sheet are investigated for a case study of the aircraft-based experiment KABEG (Katabatic wind and boundary layer front experiment around Greenland) in the area of southern Greenland in April/May 1997. Monthly mean structures and individual contributions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 18 publications
2
33
1
Order By: Relevance
“…Also the Greenland surface wind velocities in summer are generally lower than in winter, which can be attributed to the strength in the katabatic forcing (Ettema et al, 2010), as in winter strong radiative cooling over the high-elevation ice dome results in a larger amount of cold dense air masses which are accelerated downslope. Overall, the local and large-scale circulation simulated in EEMpd are in good agreement with previous studies describing the present atmospheric flow over and around Greenland based on observations (Steffen and Box, 2001;Heinemann and Klein, 2002) or climate models (Ettema et al, 2010;Hakuba et al, 2012).…”
Section: Atmospheric Circulation In Eempdsupporting
confidence: 78%
See 2 more Smart Citations
“…Also the Greenland surface wind velocities in summer are generally lower than in winter, which can be attributed to the strength in the katabatic forcing (Ettema et al, 2010), as in winter strong radiative cooling over the high-elevation ice dome results in a larger amount of cold dense air masses which are accelerated downslope. Overall, the local and large-scale circulation simulated in EEMpd are in good agreement with previous studies describing the present atmospheric flow over and around Greenland based on observations (Steffen and Box, 2001;Heinemann and Klein, 2002) or climate models (Ettema et al, 2010;Hakuba et al, 2012).…”
Section: Atmospheric Circulation In Eempdsupporting
confidence: 78%
“…In addition, the area of strongest surface winds follows the ice sheet margin (e.g., compare EEMpd and EEMr3 in Fig. 7) since the steep slopes have the largest katabatic potential (Heinemann and Klein, 2002). In contrast, the areas which become flat and ice-free (e.g., northern Greenland in EEMr2) experience a drastic reduction in surface wind speed.…”
Section: Atmospheric Circulation With Reduced Grismentioning
confidence: 99%
See 1 more Smart Citation
“…As the third largest mountain range in the Northern Hemisphere, it has an important influence on the local air flow and plays a major role in gravity-wave generation (Petersen et al, 2005), cyclogenesis (Kristjánsson and McInnes, 1999) and the formation of katabatic flows (Heinemann and Klein, 2002). Furthermore, interactions between Greenland and the cyclones passing close by on the North Atlantic storm track give rise to a number of topographically forced weather systems such as barrier flows and tip jets (Moore and Renfrew, 2005;Renfrew et al, 2008;Renfrew et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Heinemann and Klein, 2002). Klein and Heinemann (2002) suggested that convergence of the outflowing air from the katabatic flow in the valleys of east Greenland might be responsible for the formation of mesocyclones over the Denmark Strait, and found support for this view from model simulations.…”
Section: Introductionmentioning
confidence: 72%